A 10-year cohort study of 175 primary gastrointestinal lymphoma cases in Thailand: clinical features and outcomes in the immunochemotherapy era. Issue 1 (1st January 2021) - Owattanapanich, Weerapat; Ruchutrakool, Theera; Pongpruttipan, Tawatchai; Maneerattanaporn, Monthira
ABSTRACT: Background: Primary gastrointestinal lymphoma (PGIL), an uncommon subtype of lymphoma, accounts for 1%–4% of gastrointestinal cancers. This study, therefore, aimed to investigate the current 10-year epidemiology and outcomes of PGIL. Methods: This retrospective study involved a hospital-based chart review to analyze the epidemiology, clinical features, predisposing factors, and clinical outcomes of patients diagnosed with, and treated for, PGIL. Data covering 10 years was collected of Thai patients aged ≥ 15 years who had been diagnosed as PGIL with pathological confirmation and treated at Siriraj Hospital, Thailand. Results: A total of 175 PGIL patients were enrolled. Their median age was 60 years (range, 20–98), with a male predominance. The stomach was the most common site of gastrointestinal (GI) organ involvement by lymphoma (38.9%), followed by the small intestine (23.4%) and multiple sites of GI involvement (23.4%). Diffuse large B-cell lymphoma (DLBCL) had the highest proportion of PGIL, accounting for 61.1%. The median patient follow-up time was 13.9 months (range: 0–104.9 months). The median overall survival (OS) of PGIL patients was not reached during the 10 years, with a 5-year OS of 64.4%. The probability of having a better OS was demonstrated in patients with a good performance status who received a rituximab-containing regimen. Conclusions: The stomach was the most common site of lymphoma involvement in the GI tract, with DLBCL accounting for the highest proportion of those patients. The long-term survival outcome was significantly improved in patients with good performance status and rituximab exposure. Trial registration Not applicable.